The Opportunities and Challenges of Digitizing Government-to-Person Payments - Klapper, Leora; Singer, Dorothe (Published by Oxford University Press on behalf of the World Bank, 2019)
This paper reviews evidence on the benefits and challenges faced by governments migrating from cash to digital (electronic) government-to-person (G2P) payments. When supported by an appropriate consumer financial protection framework, digital payments enable confidential and convenient financial services, which can be especially important for women. By shifting government wages and social transfers into accounts, governments can lead by example. Digitizing G2P payments has the potential to dramatically reduce costs, increase efficiency and transparency, and help recipients build familiarity with digital payments. Digital wage and social transfer payments can also provide the on-ramp to financial inclusion and in many cases the first account that the recipient has in her own name and under her control. However, digitizing G2P payments is not without its challenges. Most importantly, digitization may require significant up-front investments in building an adequate physical payment infrastructure that is able to process such payments, as well as a financial identification system and a consumer protection and education framework to ensure that recipients have safe, reliable, and affordable access to the digital payment system.